IOT Based Outdoor Manhole Detection and Monitoring System - Karunananttha Gunasegeran; Mohd Hakimi Bin Zohari (Progress in Engineering Application and Technology, 2025)
The IoT-Based Outdoor Manhole Detection and Monitoring System aims to enhance the safety and efficiency of municipal infrastructure maintenance through real-time monitoring. Traditional manual inspections are labour-intensive, time-consuming, and prone to errors, which can lead to accidents and costly repairs. This system integrates IoT technology, using sensors and a microcontroller to monitor key parameters such as gas concentration, water level, temperature, and lid displacement in areas like manholes, landfills, and farm ponds. Data is processed and transmitted via cloud platforms or mobile applications, enabling timely alerts and responses. By reducing the need for manual checks, the system minimizes risks to workers and the public. Its scalable design allows for easy integration with smart city systems, promoting environmental sustainability and public safety.